Who is she? Changes in the person context affect categorization - Goldenberg, Elizabeth; Sandhofer, Catherine M. (Frontiers in Psychology, 2013)
Changes between the learning and testing contexts affect learning, memory, and generalization. We examined whether a change (between learning and testing) in the person children were interacting with affects generalization. Three, 4-, and 5-year-old children were trained on eight novel noun categories by one experimenter. Children were tested for their ability to generalize the label to a new category member by either the same experimenter who trained them or by a novel experimenter. Three-year-old children’s performance was not affected by who they were tested by. Four- and 5-year-old children’s performance was lower when tested by the novel experimenter. The results are discussed in terms of source monitoring and the effect of perceptual context change on category generalization.